Pengaruh Berat Volume terhadap Sifat Fisis dan Mekanis Bata Ringan CLC - Sutandar, Erwin (Universitas Ibn Khaldun, 2025)
To reduce the weight of a structure for the purposes of lightweight construction on clay (soft) and peat, an innovation is required. Priority one is the self-weight of the structure. A method for reducing the weight of construction is to reduce the weight of the wall, particularly the wall made of red brick, which weighs 1500 kg/m3 s/d 2000 kg/m3, and cement brick, which weighs 950 kg/m3 s/d 1000 kg/m3. Then came the innovation of CLC lightweight concrete bricks, as the technology is so simple that small to medium-sized businesses can produce them. In addition to comparatively accessible raw materials, this technology is also more environmentally benign (green technology). CLC (Cellular Lightweight Concrete) is produced by combining cement, sediment, water, chemical admixture, and infill material consisting of air-produced foam such as micro-sized detergent foam (micro bubbles) or foam agent. Based on the research conducted with varying amounts of foam, the lightweight concrete brick weighs only 400 kg/m3 s/d 1200 kg / m3. When compared to red bricks and cement bricks, the weight of lightweight concrete bricks is nearly half that of red bricks and cement bricks. As a consequence of a decrease in the volume of the bataringan's weight, the pressure has diminished. And the batringan's physical and mechanical properties will also change